2012
DOI: 10.1007/s00253-012-4144-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficient surface modification of biomaterial to prevent biofilm formation and the attachment of microorganisms

Abstract: Biomaterials play a fundamental role in disease management and the improvement of health care. In recent years, there has been a significant growth in the diversity, function, and number of biomaterials used worldwide. Yet, attachment of pathogenic microorganisms onto biomaterial surfaces remains a significant challenge that substantially undermines their clinical applicability, limiting the advancement of these systems. The emergence and escalating pervasiveness of antibiotic-resistant bacterial strains makes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
134
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(143 citation statements)
references
References 160 publications
(157 reference statements)
2
134
0
1
Order By: Relevance
“…2,21,22 However, information on the effect of nanoHA surface properties on bacterial adhesion and biofilm formation is scarce. 20 In this work, the purpose was to study the influence of nanoHA surface characteristics in S. epidermidis RP62A biofilm formation. Therefore, two different initial inoculum concentrations (Ci) were used in order to check if these Ci would affect the biofilm formed on nanoHA surfaces differing exclusively on the effect of different sintering temperatures, while both keeping grain size within the nanoscale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,21,22 However, information on the effect of nanoHA surface properties on bacterial adhesion and biofilm formation is scarce. 20 In this work, the purpose was to study the influence of nanoHA surface characteristics in S. epidermidis RP62A biofilm formation. Therefore, two different initial inoculum concentrations (Ci) were used in order to check if these Ci would affect the biofilm formed on nanoHA surfaces differing exclusively on the effect of different sintering temperatures, while both keeping grain size within the nanoscale.…”
Section: Discussionmentioning
confidence: 99%
“…While evidently detrimental to the healing process and overall wellbeing of the patient, bacterial attachment, while ensuring the formation of a biofilm, may also damage the performance of the device. 20 NanoHA has been used as coating or bone substitute in orthopaedic devices, due to its properties such as biocompatibility, bioactivity, osteoconductivity and osteoinduction. 2,21,22 However, information on the effect of nanoHA surface properties on bacterial adhesion and biofilm formation is scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In biomedical field, plasma coatings can be used to afford material chemical or mechanical protection, impart biocompatibility and antimicrobial activity, and for drug delivery. 5,6 In electronics, films from organic precursors have been used to replace conventional inorganic materials to produce superior organic and hybrid devices. Organic electronics offer several advantages over conventional silicon electronics, such as flexibility and low cost fabrication from solution, allowing production of flexible, lightweight, self-illuminating displays based on Organic Light Emitting Diode (OLED) and Organic Field Effect Transistor (OFET) devices and low-cost Organic Photo-Voltaic (OPV) and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Then, some reactive oxygen species (ROS) are produced. One target is the outer membrane of bacteria (Bazaka et al, 2012). Observation of cells emptied of their cytoplasmic content suggested that the outer membrane was damaged.…”
Section: Discussionmentioning
confidence: 99%